Can Price Sway Children Preference? Preliminary Experiment among Malay Children. - Dahari, Zainurin Bin; Kokash, Husam A.; Sulaiman, Fadilah (International Review of Management and Marketing, 2017)
This study deals with young Malay children’s behavior concerning money. The objectives are to determine the children knowledge of money value, source of their money knowledge and whether price can sway their preference. The literature on Children Socialization and Information Processing Theory in consumer behavior suggests that most young children under 8 are not cognitively skilled about pricing and to use price in decision making. An interview has been conducted to gain the children insight about their money value and the source of money knowledge. In order to test for the effects of price, an experiment has been conducted to determine their preference. The study has found that children didn’t have strong knowledge of money value and pricing of products not dependably influence their preference. In order to conclude for a better generalization, this preliminary finding could be used as a initial point for a larger scale of research in term of sample size, range of aged group and ethnicity. Keywords: Price, Children, Preference JEL Classifications: M31, M39